Calming the Mind and Discerning the Real: Buddhist Meditation: and the Middle View from the Lam rim chen mo of Tson-kha-pa - Chapple, Christopher (Journal of Dharma, 1980)
Tson-kha-pa, Calming the Mind and Discerning the Real: Buddhist Meditation: and the Middle View from the Lam rim Chen mo of Tson-kha-pa, Translated by Alex Wayman (New York: Columbia University Press, 1978), pp. + ix 512.